2021
DOI: 10.3390/ijms222312671
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Aggregation of 16 kDa Gamma-Zein during Seed Maturation in Transgenic Arabidopsis thaliana

Abstract: Prolamins constitute a unique class of seed storage proteins, present only in grasses. In the lumen of the endoplasmic reticulum (ER), prolamins form large, insoluble heteropolymers termed protein bodies (PB). In transgenic Arabidopsis (Arabidopsis thaliana) leaves, the major maize (Zea mays) prolamin, 27 kDa γ-zein (27γz), assembles into insoluble disulfide-linked polymers, as in maize endosperm, forming homotypic PB. The 16 kDa γ-zein (16γz), evolved from 27γz, instead forms disulfide-bonded dispersed electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…The particularly strong effect of 16γz suggests that, with respect to its 27γz parent gene, this recently evolved prolamin is more dependent on partner zeins for acquiring a folded conformation that abolishes BiP binding. This is consistent with the observation that, during maturation and desiccation of transgenic Arabidopsis seeds, 16γz becomes progressively insoluble also in reducing buffers, indicating disordered aggregation ( Arcalis et al, 2021 ).…”
Section: Tailored Upr Induction For Each Type Of Storage Proteinsupporting
confidence: 91%
“…The particularly strong effect of 16γz suggests that, with respect to its 27γz parent gene, this recently evolved prolamin is more dependent on partner zeins for acquiring a folded conformation that abolishes BiP binding. This is consistent with the observation that, during maturation and desiccation of transgenic Arabidopsis seeds, 16γz becomes progressively insoluble also in reducing buffers, indicating disordered aggregation ( Arcalis et al, 2021 ).…”
Section: Tailored Upr Induction For Each Type Of Storage Proteinsupporting
confidence: 91%
“…This is well in agreement with earlier observations in Arabidopsis leaves where 16-kDa-γ-zein formed dispersed electron-dense threads enlarging the ER lumen without assembling into PBs, and only when co-expressed with 27-kDa-γ-zein it co-assembles with the latter into insoluble polymers ( Mainieri et al., 2018 ). In transgenic Arabidopsis seeds 16-kDa-γ-zein formed more compact aggregates, but remained largely insoluble in reducing conditions, also suggesting that 16-kDa-γ-zein is unable to form well-ordered polymers on its own but relies on the ability of 27-kDa-γ-zein to drive self-assembly ( Arcalis et al., 2021 ). Although 16-kDa-γ-zein most likely evolved through gene duplication of 27-kDa-γ-zein ( Xu and Messing, 2009 ), this different behavior may be explained by the loss of the repeat region as well as some cysteine residues reducing the strength of its intermolecular interactions ( Mainieri et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of the canonical HDEL/KDEL retention or retrieval signals, prolamins destined for ER-derived PBs fail to escape from the ER in plant seeds and even vegetative tissues when ectopically expressed [34][35][36][37]. Domain truncation and mutagenesis studies have identified several conserved sequence domains and key amino acid residues essential for the ER retention of prolamins, such as the N-terminal proline-rich tandem repeat domain in maize zeins that forms an amphipathic helix, which interacts with the ER surface [38].…”
Section: Er-derived Protein Bodies: a Major Destination For Prolaminsmentioning
confidence: 99%